Prognosis of mucinous colon cancer is determined by histological biomarkers rather than microsatellite instability. Issue 2 (3rd November 2022) - van Zwam, Peter H.; Vink‐Börger, Elisa M.; Bronkhorst, Carolien M.; de Bruine, Adriaan P.; van der Wurff, Anneke A.; Rutten, Harm J.T.; Lemmens, Valery E.P.P.; Nagtegaal, Iris D.; Hugen, Niek
Abstract : The prognostic value of microsatellite instability (MSI), as well as other histological characteristics such as lymphovascular invasion (LI), perineural invasion (PNI) and extramural vascular invasion (EMVI), is unclear in colorectal mucinous carcinoma (MC). This study aims to determine the relevance of these factors in MC patients and analyses the role of MSI in stage III MC patients treated with adjuvant chemotherapy. A cohort of 650 patients diagnosed with stages I–IV colonic MC from 2000 to 2010 was selected from PALGA, the nationwide Dutch pathology databank. Histopathology was revised and mismatch repair (MMR) status determined. Univariate and multivariate survival analyses were performed. Deficient MMR (dMMR) was found in 33% of MCs and correlated with female gender and right‐sidedness, but also with lower tumour stage (stages I/II: 73.2 versus 47%; P  < 0.0001) and the absence of EMVI (9.7 versus 23.7%; P  < 0.0001) and PNI (5.6 versus 12.7%; P  = 0.005). On univariate analysis OS was better for dMMR MC than for proficient MMR (pMMR) MC (median OS of 9.7 versus 5.0 years; P  = 0.009), but MMR status was no longer a relevant prognostic factor on multivariate analysis [hazard ratio (HR) = 0.91, 95% confidence interval (CI) = 0.70–1.18]. Stage III MC patients benefited from adjuvant chemotherapy, and dMMR status was associated with better OS in this group (HR = 0.35, 95% CI = 0.13–0.94). EMVI, LI and PNI, but not MMR, status are independent prognostic factors for survival in MC patients. Stage III MC patients benefit from adjuvant chemotherapy and dMMR status is associated with improved survival when adjuvant chemotherapy is given. Abstract :